Asesmen Perkembangan Sosial Emosional Anak Usia 5–6 Tahun Menggunakan Skala Penilaian Bertema Alat Transportasi - Royani Oktavia Sipahutar; Frika Utari; Putri Hairunisa; Jesika Amelia Br Sembiring (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
Assessment of early childhood social-emotional development plays a crucial role in preparing children for the next stage of education. However, many early childhood institutions still rely on simple and unsystematic assessment methods. This study aims to implement a rating scale as an assessment tool for the social-emotional development of children aged 5–6 years in the context of a transportation-themed play activity. A descriptive quantitative approach was used, involving 9 children assessed with a validated observation instrument. The results indicate that most children exhibited very good social-emotional development. For the indicator of willingness to join group play, 6 children were in the Very Well Developed (BSB) category. For the ability to play cooperatively, 7 children were rated BSB. Regarding the expression of joy when sharing experiences, 6 children were also categorized as BSB. The rating scale proved effective in systematically and objectively documenting children's social-emotional behaviors and served as a foundation for designing follow-up learning strategies. This study recommends integrating social-emotional assessments into daily practice and fostering collaboration between teachers and parents to optimize children's development.